A formação de professores no Brasil: uma genealogia dos modelos de formação - Feltrin, Tascieli (2022)
Abstract: This research, linked to Research Line 1 of the Postgraduate Program in Education at UFSM, this research aimed to answer the following question: How and when does Teacher Training take place as a field of knowledge and as a device of power in Brazil? Operating with the concepts of provenance and emergence (FOUCAULT, 1996); deterritorialization, and reterritorialization (DELEUZE; GUATTARI, 1997), this research is methodologically based on the Genealogical approach (FOUCAULT, 1996) and proposes two movements: a first movement (deterritorialization) focuses on the study of the Native American group's knowledge production - knowledge submitted by the emergence of schooling - with emphasis but also considering other presences such as Afro-Brazilians; This movement presents evidence and processes that allow us to understand how teacher training was constituted over time – its provenance and emergence. From this perspective, the object of this study is the constitution of the teacher training field in Brazil, and the specific objectives are: To investigate the conditions of possibility that allowed the deterritorialization of native knowledge; To analyze the emergency conditions of Teacher Training as a field of expertise; To identify how power relations operate in the field of Teacher Training; To understand how these relationships act on individuals in training; and to situate the emergence of Teacher Training as a device of power in Brazil. As research files, we used official documents related to the curricular organization of undergraduate courses, public policies related to the organization of higher and basic education, historical educational works, and documentary, photographic or other records that help to understand the proposed theme.